Spiny Prey, Fortunate Prey. Dorsal Spines Are an Asset in Intraguild Interactions among Lady Beetles - Hautier, Louis; San Martin, Gilles; Jansen, Jean-Pierre; Branquart, Etienne; Grégoire, Jean-Claude (Frontiers in Ecology and Evolution, 2017)
The Multicolored Asian Ladybird, Harmonia axyridis, is an extremely successful invasive species. Here we suggest that, in addition to many other traits, the dorsal spines of its larvae contribute to their success, as suggested by behavioural observations of agonistic interactions between H. axyridis and European coccinellids. In coccinellids, the role of dorsal spines in these interactions has been poorly studied and they could be a physical protection against intraguild predators. Dorsal spines of second instar H. axyridis larvae were removed with micro-scissors, which resulted in spineless larvae after moulting (spineless group). These larvae were then exposed to starved Coccinella septempunctata larvae. Two control categories were also submitted to interactions: H. axyridis larvae with all their spines (control group) and with their spines, but injured by pin stings (injured group). Spine removal at the second instar did not hamper H. axyridis development. The bite rate by C. septempunctata was significantly higher on the spineless H. axyridis and more dorsally located compared to the control and injured groups, while no bite rate difference was observed between the injured and the control group. Our results suggest that in addition to behavioural and chemical defenses, the dorsal spines play a significant protective role against bites. Therefore, spines in ladybirds could be considered as a morphological defense against intraguild predation. In H. axyridis, these defenses might contribute to its success in food resources already exploited by other guild members and thus further facilitate the invasion of new areas.